2017
DOI: 10.1038/modpathol.2016.173
|View full text |Cite
|
Sign up to set email alerts
|

Papillary thyroid carcinoma with nodular fasciitis-like stroma and β-catenin mutations should be renamed papillary thyroid carcinoma with desmoid-type fibromatosis

Abstract: Various histological variants of papillary thyroid carcinoma have been reported, some with clinical implications, some with peculiar, sometimes misleading morphologies. One of these rare and poorly characterized variants is papillary thyroid carcinoma with nodular fasciitis-like stroma, of which fewer than 30 cases have been documented, mostly as isolated reports. It is a dual tumor comprising a malignant epithelial proliferation that harbors typical features of conventional papillary thyroid carcinoma, admixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(62 citation statements)
references
References 33 publications
4
56
1
1
Order By: Relevance
“…We agree with the proposal by Rebecchini et al [5]. Microscopically, the stromal component is consistent with DTF and not with nodular fasciitis.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…We agree with the proposal by Rebecchini et al [5]. Microscopically, the stromal component is consistent with DTF and not with nodular fasciitis.…”
Section: Discussionsupporting
confidence: 81%
“…Toti et al [15] and Michal et al [16] reported that the DTF components were present at the tumor periphery. In the cases reported by Terayama et al [17], Ginter, et al [12], and Rebecchii et al [5], the distributions were central, mixed, and diffuse, respectively. In our study, 4, 1, 7, and 2 cases of PTC-DTF exhibited central, peripheral, mixed, and diffuse patterns, respectively.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Recently, Rebecchini et al [2] reported a mutation in exon 3 of CTNNB1 in the mesenchymal components of two cases of PTC with fibromatosis/nodular fasciitis-like stroma. The involvement of the activated Wnt/β-catenin pathway has not been observed in nodular fasciitis, so they proposed a more suitable term for this variant: PTC with desmoid-type fibromatosis (PTC-DTF) [2]. This study was designed to evaluate the prevalence of CTNNB1 mutations in more cases of PTC-DTF exhibiting aberrant nuclear and cytoplasmic immunoreactivity for β-catenin.…”
Section: Introductionmentioning
confidence: 99%
“…Because aberrant nuclear and cytoplasmic immunoreactivity for β-catenin is observed in the mesenchymal components, it has been suggested that activated Wnt signaling is involved in the stromal overgrowth of this variant [2].…”
Section: Introductionmentioning
confidence: 99%